TANTANGAN DAN KESIAPAN UKM BATIK LAWEYAN DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN 2015 - Herning Suryo, Indri Yani Claudia Margareta, Christy Damayanti & (Transformasi, 2016)
Most of Indonesians speak up their inability in facing the free trade era in Southeast Asia,including the SMEs as one of the Indonesia‟s economy props. The Batik Laweyan SMEs are apart of Indonesian facing the challenges in AEC implementation and a part of Surakarta‟seconomic stability. Therefore, this thesis explained about the faced challenge and the readinessof Batik Laweyan SMEs in AEC 2015.This thesis is written by using descriptive qualitative method. There are two kinds of data usedin this research, i.e. primary and secondary data. The primary data is collected through directlyinterview to Kepala Dinas Perdagangan dan Perindustrian Kota Surakarta, Kepala DinasKoperasi dan UMKM Kota Surakarta, and two owners of Batik Laweyan SMEs. Data whichhave been collected are reducted, explained, and verified in its analysis.Based on this research, collected data show that SMEs are not only important for Indonesia, butalso ASEAN, so being the most concern in AEC. However, Batik Laweyan SMEs have not feltyet the impact of AEC. There is no significant escalation on sale. The problems faced by BatikLaweyan SMEs are the classical issues which have been happened for a long time.In this research, it can be concluded that Batik Laweyan SMEs face the challenge, such asrivalry price, minimum promotion, cultural preservation, and engagement inter-SMEs.However, Batik Laweyan SMEs have had the good readiness. It is the result of synergy betweenthe local government and Batik Laweyan SMEs.Keywords : Batik Laweyan SMEs, Challenges, AEC, Readiness